Dark matter distribution in Milky Way analog galaxies - Isídio, Natanael G. de; Menéndez-Delmestre, K.; Gonçalves, T. S.; Grossi, M.; Rodrigues, Davi C.; Garavito-Camargo, N.; Araujo-Carvalho, A.; Beaklini, P. P. B.; Cavalcante-Coelho, Y.; Cortesi, A.; Quiroga-Nuñez, L. H.; Randriamampandry, T. (The astrophysical journal, 2024)
Our current understanding of how dark matter (DM) is distributed within the Milky Way (MW) halo, particularly in the solar neighborhood, is based on either careful studies of the local stellar orbits, model assumptions on the global shape of the MW halo, or from direct acceleration measurements. In this work, we undertake a study of external galaxies, with the intent of providing insight into the DM distribution in MW-analog galaxies. For this, we carefully select a sample of galaxies similar to the MW, based on maximum atomic hydrogen (H i) rotational velocity ( km s−1) and morphological type (Sab-Sbc) criteria. With a need for deep, highly resolved H i, our resulting sample is composed of five galaxies from the VLA Imaging of Virgo in Atomic Gas (VIVA) survey and The H i Nearby Galaxy Survey (THINGS). To perform our baryonic analysis, we use deep mid-IR images at 3.6 and 4.5 μm from the Spitzer Survey of Stellar Structures in Galaxies (S4G). Based on the dynamical three-dimensional modeling software 3D-Based Analysis of Rotating Objects via Line Observations (3D-BAROLO), we construct rotation curves (RCs) and derive the gas and stellar contributions from the galaxy's gaseous and stellar disks' mass surface density profiles. Through a careful decomposition of their RCs into their baryonic (stars, gas) and DM components, we isolate the DM contribution by using a Markov Chain Monte Carlo-based approach. Based on the Sun's location and the MW’s R 25, we define the corresponding location of the solar neighborhood in these systems. We put forward a window for the DM density (ρ dm = 0.21-0.55 GeV cm−3) at these galactocentric distances in our MW analog sample, consistent with the values found for the MW’s local DM density, based on more traditional approaches found in the literature.
Veröffentlichung: 6. August 2024
Gesehen am 14.07.2025